2020
DOI: 10.1002/hpm.3032
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary academic perspectives during the COVID‐19 pandemic

Abstract: To date, the outbreak of the novel coronavirus (COVID-19) has infected more than 5 million people and caused around 350 000 deaths globally. In most countries, the world as we knew it came to a sudden stop and this led to the biggest shift of employees to remotely conduct their work. Academic institutions were extensively affected, as teaching and assessment activities were hampered, and graduation ceremonies were cancelled. In addition, there was an imminent disruption in academic and research activities incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…Larger universities may have the option of utilizing third party exam proctoring systems such as ProctorU or Examinty as suggested in Iyer et al (2020), but smaller schools often do not have the resources to implement learning management systems for exam monitoring and beyond. In Kuwait, private universities transitioned to remote learning, but public universities postponed spring semesters until August 2020 (Al-Taweel et al 2020). The decision to postpone was multifaceted, and included regulations surrounding accreditation of online programs, and the perception that online education is inferior to face-to-face course work.…”
Section: Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Larger universities may have the option of utilizing third party exam proctoring systems such as ProctorU or Examinty as suggested in Iyer et al (2020), but smaller schools often do not have the resources to implement learning management systems for exam monitoring and beyond. In Kuwait, private universities transitioned to remote learning, but public universities postponed spring semesters until August 2020 (Al-Taweel et al 2020). The decision to postpone was multifaceted, and included regulations surrounding accreditation of online programs, and the perception that online education is inferior to face-to-face course work.…”
Section: Technologymentioning
confidence: 99%
“…Due to the speed with which the virus spread, the almost instantaneous shift from face-to-face teaching to remote coursework did not allow faculty to prepare adequately (Al-Taweel et al 2020). Moreover, faculty have had generally negative attitudes about remote instruction, specifically in courses where "hands-on" experiences, such as fieldwork and labs, are utilized (Barton 2020; Nic Dhonncha and Murphy 2020), although some remote teaching methods were viewed as effective (Barton 2020) such as asynchronous instruction that involves little to no interaction with the instructor or peer.…”
Section: Faculty Perceptionsmentioning
confidence: 99%
“…In the spring semester of 2020, colleges and universities across the United States suddenly closed access to their campuses due to the COVID-19 pandemic ( 1 – 3 ). During this time, university stakeholders were dealing with the impacts of the pandemic as well as the transition to Emergency Remote Teaching (ERT) ( 2 , 4 ). Campus closures during the COVID-19 pandemic have affected STEM research faculty and students in particular as not only did many campuses switch to online teaching, but many universities in the United States also ceased all nonessential research operations.…”
Section: Introductionmentioning
confidence: 99%
“…Discussions related to campus closures focus heavily on the impacts on faculty and undergraduate students in both popular press and the initial wave of publications related to higher education during the pandemic (5)(6)(7)(8). These range from work-related stressors, such as Internet challenges and lack of preparation for ERT (4,9), to psychological stressors including how quarantining and social isolation can have serious effects on mental health, such as insomnia, post-traumatic stress disorder, and low mood (8,10,11). Previous work on the impact of tragedies and disasters on college students has shown that there are emotional and cognitive repercussions even on those who are not directly affected by the traumatic event in question (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The International Civil Aviation Organization (ICAO) confirmed that passenger traffic suffered a dramatic 60 per cent drop over 2020, bringing air travel totals back to 2003 levels (International Civil Aviation Organization, 2021). In higher education institutions, students are among those impacted by these measures such as the social restrictions -including social distancing and self-isolation measures (Al-Taweel et al, 2020). For the aviation students, that has slowed the hiring process for the recent graduates as well as the hands-on training such flight instructions (Ley, 2020).…”
Section: Introductionmentioning
confidence: 99%